Heavy metal concentrations in surface sediments and tissues of Periophthalmodon schlosseri (Pallas, 1770) and Arius sumatranus (Bennett, 1830) from selected sites in Peninsular Malaysia - Jafaru Malam, Ahmed (2018)
Heavy metals have been studied extensively in sediments and tissues of aquatic biota due to their toxic effects and non biodegradable nature in aquatic environment. Heavy metals concentrations in surface sediments and their effects on giant mudskipper Periophthalmodon schlosseri Pallas 1770 and marine catfish Arius sumatranus Bennet 1830 from selected sites in Peninsular Malaysia were investigated. The anthropogenic source of heavy metal pollution in the selected sites was examined by geochemical fractionation and relationships between histological structures and reduced glutathione; GSH were determined. Triplicate samples of surface sediment, P. schlosseri and A. sumatranus were collected from selected sampling sites in Peninsular Malaysia. The mudskipper lives directly on the surface sediment and feeds on the organisms found there while the marine catfish lives just above the surface sediments and feeds on the bottom organisms also. The two species are readily available in the selected sampling sites. The sites include; Bagan Lalang (BL) in Selangor, Kuala Gula (KG) in Perak, Kuala Juru (KJ) in Penang, Sungai Puluh (SP) in Klang and Sungai Tiga (ST) in Johor in 2010, 2012 and 2014 respectively. Surface sediments and fish samples were collected in March and June 2010, February and May 2012 and March and May 2014 from the sampling sites. Geochemical speciation and total concentrations of heavy metals in sediments were extracted using a modified 4- step sequential extraction technique (SET) (Easily, freely or leachable and exchangeable fraction (EFLE), Acid reducible, oxidisable organic and resistant fractions) and aqua-regia procedures (QA/QCT). Histopathological examination of some tissues (liver, muscles and gills) was carried out. Reduced Glutathione concentration was determined in liver, gill, muscle and kidney of P. schlosseri and A. sumatranus using QuantiChrom Glutathione Assay Kit (Catalog no. DIGT-250 from BioAssay Systems Company, USA). The data obtained was analysed using analysis of variance (ANOVA) at 95% confidence interval, multiple comparison test was carried out using Duncan’s Multiple Range Test. Pearson’s correlation coefficient (r) was used to test the relationships between heavy metals and tissues of the fish species and GSH levels. Results obtained shows that the mean total concentration of the metals in surface sediment was significantly (p<0.05) highest for Cd at SP 2.21±0.43 and lowest at BL 0.91±0.22, while Cu, Ni, Pb, V and Zn were 42.96±0.45 at KJ and 8.44±0.11 at SP, 34.79±0.75at KJ and 10.79±0.69 at ST, 42.72±0.89 at KJ and 21.58±1.19 at BL, 33.81±5.53 at ST and 20.02±1.43 at BL, 214.82±1.54 at KJ and 70.75±3.72 at BL μg/g dry weight respectively. Geochemical fractions of metals indicates that of all the metals under the present study only Cu has low anthropogenic contribution as its resistant fractions were higher than the non-resistant fractions in all the sites (except in BL) with highest in KJ (67.88%) and lowest in BL (46.25%). Nonresistant fractions from all the metals except Cu and in all the other sampling sites were higher than the resistant fractions (Cd 80.33% at SP, Ni 75.44% at KJ, Pb 65.01% at SP, V 76.89% at KG and Zn 86.54% at BL). The concentrations of Cd from all the sampling sites were above the values of ERL for Cd (1.2 μg/g) except for BL (0.91 μg/g). Concentrations of Cu in all the sampling sites except for KJ (42.96 μg/g) were below the ERL value of Cu (34 μg/g) and below the ERM value of Cu (270 μg/g). Nickel concentrations at both KG (21.63 μg/g) and KJ (34.79 μg/g) were above the ERL value (20.9 μg/g) while all other sites were below the ERL value and below ERM value of Ni (51.6 μg/g). The concentrations of Pb in all the sampling sites were below both ERL (46.7 μg/g) and ERM (218 μg/g) values while Zn concentrations in KJ (214.82 μg/g) was above the ERL value of Zn (150 μg/g) but below ERM value (410 μg/g). The highest mean enrichment factor (EF) values were recorded for Cd (50.78 at SP), Cu (2.72 at KJ), Ni (1.72 at KG), Pb (6.28 at KG), V (1.15 at KG) and Zn (5.38 at KJ). The values obtained for index of geoaccumulation were either above or below the three background concentrations used. Pollution load index (PLI) values obtained for the present study (0.98, 1.39, 2.54, 1.29 and 1.31) for BL, KG, KJ, ST and SP respectively, were higher than all the three background concentrations used. The concentration of metals in the tissues of P. schlosseri showed lowest and higest concentrations in gill (BL - 0.28 μg/g) and bone (SP - 2.12 μg/g), muscle (BL - 1.10 μg/g) and liver (ST - 5.54 μg/g), muscle (SP - 0.59 μg/g) and bone (ST - 8.340 μg/g), muscle (BL - 0.92) μg/g and bone (SP - 63.96 μg/g), scale (ST - 0.130 μg/g) and bone (BL - 1.03 μg/g) and muscle (SP - 33.84 μg/g) and skin (SP - 145.54 μg/g) for Cd, Cu, Ni, Pb, V and Zn μg/g dry weight respectively. And for A. sumatranus showed lowest and highest concentrations in skin (KG - 0.13 μg/g) and bone (SP - 1.83 μg/g), skin (SP - 0.35 μg/g) and liver (ST - 28.27 μg/g), muscle (KG - 0.19 μg/g) and bone (ST- 9.47 μg/g), skin (ST - 2.14 μg/g) and bone (KG - 57.90 μg/g), mmuscle (SP - 0.09 μg/g) and gill (SP - 1.09 μg/g) and muscle (ST - 43.78 μg/g) and liver (SP - 793.25 μg/g) for Cd, Cu, Ni, Pb, V and Zn μg/g dry weight respectively. For both species the concentrations of metals in the tissues indicate significant differences (p<0.05) between the sampling sites except in few cases which shows non-significant differences (p>0.05). The bioconcentration factors (BCF) calculated for both species designate that some of the tissues were grouped as macro concentrators. In P. schlosseri Cu and V had the highest average values of BCF in gill (3.80) and bone (6.08) respectively while in A. sumatranus V and Zn had the highest average BCF values both in liver (6.87 and 10.51) correspondingly. The Pearson’s correlation coefficient (r) analysis between metal concentrations in the tissues of both species and geochemical fractions of sediment indicate significant (p<0.05) correlations in some fractions signifying that both species are suitable for use as biomonitoring agents for heavy metal pollution in the region. Histopathological examinations of some tissues of both species indicated from mild, moderate to severe forms of alterations of the tissues such as congested vessels, vacuolation of hepatocytes, matting of villi (gill synechiae) and heterophil infiltration. The liver had the highest mean GSH value of 207.72 and gill had the lowest mean GSH values of 110.15 in P. schlosseri and A. sumatranus respectively. Domination of non-resistant over resistant fraction indicates anthropogenic contribution of the metals in the study areas. Overall results of concentrations of heavy metals, GCF and indices of pollution in the surface sediment signifies that all the sampling sites used in the present study could be regarded as either unpolluted, moderately or strongly polluted. The lowest concentration of heavy metal in this study displays higher PLI values compared to the other three background concentrations used signifying anthropogenic input of heavy metals in the sampling sites.